2016
DOI: 10.1007/978-3-319-26300-7_9
|View full text |Cite
|
Sign up to set email alerts
|

The Experience of Coincidence: An Integrated Psychological and Neurocognitive Perspective

Abstract: In this chapter, we focus on psychological and brain perspectives on the experience of coincidence. We first introduce the topic of the experience of coincidence in general. In the second section, we outline several psychological mechanisms that underlie the experience of coincidence in humans, such as cognitive biases, the role of context and the role of individual differences. In the third and final section we formulate the phenomenon of coincidence in the light of the unifying brain account of predictive co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…A common denominator of these different measures is the tendency to perceive illusory patterns in random noise or between unrelated events (van Elk, Bekkering, & Friston, 2015). For instance, many conspiracy beliefs are characterized by the idea that unexplained and seemingly random details of a major event (e.g., the time it took the ambulance to take Princess Diana to the hospital) must have a cause at deeper level (e.g., the ambulance was intentionally delayed because of a conspiracy by the secret service; cf.…”
Section: Discussionmentioning
confidence: 99%
“…A common denominator of these different measures is the tendency to perceive illusory patterns in random noise or between unrelated events (van Elk, Bekkering, & Friston, 2015). For instance, many conspiracy beliefs are characterized by the idea that unexplained and seemingly random details of a major event (e.g., the time it took the ambulance to take Princess Diana to the hospital) must have a cause at deeper level (e.g., the ambulance was intentionally delayed because of a conspiracy by the secret service; cf.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have investigated how individual differences in religiosity relate to agency detection and mentalizing biases. Studies show, for example, that paranormal believers compared to skeptics have a strong tendency to report seeing meaningful patterns in random noise (Blackmore & Moore, 1994), display a bias toward detecting faces in objects (Riekki, Lindeman, & Raij, 2014), and show a bias for illusory agency detection (e.g., seeing more intentionality in randomly moving figures or dots; van Elk, 2013van Elk, , 2015b. 9 These studies, however, leave it unclear whether agency detection is a cause or a consequence of religious and paranormal beliefs (or both result from some deeper underlying tendency).…”
Section: Individual Difference Studiesmentioning
confidence: 99%
“…Others have shown that humans have a pervasive and developmentally early-emerging tendency for teleological thinking (Kelemen, 2004), and a stronger tendency for teleological thinking is in turn related to increased religiosity (e.g., Heywood & Bering, 2014). Another profound bias that has been associated with supernatural beliefs is the "experience of meaningful coincidence," whereby a seemingly random event is attributed special significance (e.g., reading a passage in the Bible that really stands out and that is interpreted as a personal message from God; van Elk, Friston, & Bekkering, 2016). These and other socio-cognitive biases have at least similar explanatory potential to agency-detection biases, when it comes to supernatural beliefs.…”
Section: Conceptual Problems With Haddmentioning
confidence: 99%
See 1 more Smart Citation
“…We will argue that the illusion of control is strongly related to a process of reinforcement learning and the detection of illusory contingencies (for review, see: van Elk, Friston, & Bekkering, 2015). In contrast, sense of agency is primarily related to a predictive process, in which the anticipated outcomes of one's actions are compared with the observed sensory consequences.…”
Section: Introductionmentioning
confidence: 97%